The Impact of Agricultural Use of Retisols on the Molecular Structure of Humic Substances - Evgeny Lodygin; Evgeny Abakumov (Agronomy, 2022)
Agricultural soil use does not only affect the amount of soil organic matter, but also the molecular composition of humic (HAs) and fulvic acids (FAs). Changed hydrothermal conditions and composition of the incoming plant residues are reflected in the rate of humification and its products. The objective of this study was to compare the molecular composition of HAs and FAs isolated from Eutric Albic Stagnic Histic Retisol (Loamic), two Eutric Albic Retisols (Loamic)—mature and arable. Plots of mature Retisols are located at a middle taiga (Komi Republic, Russia) in a bilberry-green-moss birch-spruce forest. The plot of Retisols arable is located in the fields of the Syktyvkar state farm, which is 3.3 km northeast of mature Retisol plots. The development period is about 40 years, it is sowed with a pea-oat mixture. The results obtained indicate that soil reclamation essentially increases the proportion of aromatic components and decreases the content of carboxyl and ester groups in the humic substance (HS) structure. An increased extent of hydromorphism of Retisols leads to the enrichment of HS with aliphatic fragments.